Hubungan Prenatal Yoga dengan Tingkat Kecemasan Ibu Hamil Trimester III di PMB D - Putri Yunita Sari; Zulhijriani (Jurnal Profesi Bidan Indonesia, 2024)
Background: Pregnancy is a continuous process from conception to delivery. Hormonal changes that occur in pregnant women will result in emotional changes that will cause anxiety and even depression. Anxiety and depression during pregnancy are major problems in society because of their high prevalence. According to the World Health Organization (WHO), 10% of pregnant women and 13% of postpartum mothers worldwide experience mental disorders. In developing countries, this figure is even higher, namely 15.6% during pregnancy and 19.8% after birth. According to (Yuniza et al, 2021), anxiety levels in pregnant women can be reduced with prenatal yoga. Prenatal yoga is a type of exercise for the mother's body, mind and mental health, and is very helpful in calming the mind during the third trimester. Purpose: This study aims to determine the relationship between prenatal yoga and the anxiety level of third trimester pregnant women in PMB D.Method: This research used an analytical survey design with a cross sectional approach, determining the sample using accidental sampling, namely 30 people, which took place in January - June 2023. The instruments used in this research were observation sheets and questionnaires. Data analysis used univariate analysis to determine the frequency distribution studied, namely the percentage of prenatal yoga and the anxiety level of pregnant women in the third trimester. Bivariate analysis used the Chi Square test which aims to test the relationship between prenatal yoga and the anxiety level of pregnant women in the third trimester. Results: There is a relationship between prenatal yoga and the anxiety level of third trimester pregnant women in PMB D (sig. = 0.001<0.05). Conclusion: The category of pregnant women who regularly participate in prenatal yoga is 21 people (70%), the category of anxiety level of third trimester pregnant women is normal as many as 13 people (43.3%), there is a relationship between prenatal yoga and the anxiety level of third trimester pregnant women in PMB D (sig . = 0.001<0.05)